The nucleon structure function and the quark effective potential - Trevisan, Luis A.; Tomio, Lauro [UNESP] (Elsevier B.V., 2001)
By considering a statistical model for the quark content of the nucleon, where the quark levels are generated by a Dirac equation with a harmonic scalar-plus-vector potential, we note that a good fit for the ratio between the structure functions of the neutron and proton, F-2(n)/F-2(p), can be obtained if different strengths are used for the effective confining potentials of the up and down quarks.